International Conference on Computational Intelligence for Modelling, Control and Automation and International Conference on In 2005
DOI: 10.1109/cimca.2005.1631451
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Delays in Public Transportation using Neural Networks

Abstract: The project the authors of this paper are involved in is titled "System for intelligent realtime timetable optimization and monitoring". The objective is to develop a system being able to use delay-predictions for real-timedelay-monitoring, and in the long term, for a timetableoptimization in the range of train networks. The presented paper deals with the part of the system responsible for processing existing delays in the network to generate delaypredictions for depending trains in the near future. Therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…ANN, as a basic ML method, learn from historical data to make predictions about future [113]. Peters et al [114] applied ANN to process existing delays abstracted from known operation data to generate delay predictions for depending trains shortly; this method performs well when predicting future (secondary) delays based on existing (primary) delays, and it outperforms the traditional rule-based method. Yaghini et al [115] also presented an ANN model with high accuracy to predict the delay of passenger trains in Iran; the comparison of the proposed ANN, decision trees, and multinomial logistic regression models confirm that the ANN model has high accuracy, low training time, and remarkable solution qualities.…”
Section: B: Gmmentioning
confidence: 99%
“…ANN, as a basic ML method, learn from historical data to make predictions about future [113]. Peters et al [114] applied ANN to process existing delays abstracted from known operation data to generate delay predictions for depending trains shortly; this method performs well when predicting future (secondary) delays based on existing (primary) delays, and it outperforms the traditional rule-based method. Yaghini et al [115] also presented an ANN model with high accuracy to predict the delay of passenger trains in Iran; the comparison of the proposed ANN, decision trees, and multinomial logistic regression models confirm that the ANN model has high accuracy, low training time, and remarkable solution qualities.…”
Section: B: Gmmentioning
confidence: 99%
“…This method has achieved greater forecasting accuracy compared with artificial neural networks [25]. For timetable improvement and real-time delay monitoring in a range of real train networks of the Deutsche Bahn, a delay prediction system has been developed utilising a neural network [26]. For studying and analysing large volumes of data, ML methods are growing increasingly powerful for track condition prediction, therein achieving improvements in future railway safety and service quality [27]- [29].…”
Section: Related Work a Railway Applications And Machine Learningmentioning
confidence: 99%
“…Artificial neural networks (ANNs) have been widely used to predict delays in passenger trains. On the basis of data in the Deutsche Bahn, Germany (Peters, Emig, Jung, & Schmidt, 2005) and data from 2004 to 2009 in Iran (Yaghini, Khoshraftar, & Seyedabadi, 2013) an ANN was proposed to estimate passenger train delays. However, Marković, Milinković, Tikhonov, and Schonfeld (2015) indicated that SVR is more accurate for predicting passenger train arrival delays than ANN algorithms based on Serbian Railways data.…”
Section: Literature Reviewmentioning
confidence: 99%